1999
DOI: 10.1038/sj.onc.1202866
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 and Smad4 gene mutations in hepatocellular carcinoma

Abstract: TGF-β is a negative regulator of liver growth. Smad family of genes, as mediators of TGF-β pathway, are candidate tumor suppressor genes in hepatocellular carcinoma (HCC). We studied 35 HCC and non-tumour liver tissues for possible mutations in Smad2 and Smad4 genes. Three tumours displayed somatic mutations; two in Smad4 (Asp332Gly and Cys401Arg) and one in Smad2 (Gln407Arg) genes. All three mutations were A:T → G:C transitions suspected to result from oxidative stress as observed in mitochondrial DNA. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 24 publications
1
88
0
1
Order By: Relevance
“…Also, in chronic hepatitis C infection, HCV-derived core protein associates with the Smad3 MH1 domain inhibiting its DNA-binding activity (Pavio et al, 2005). Smad2 and Smad4 gene mutations have also been identified in 5-10% HCCs (Yakicier et al, 1999;Longerich et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in chronic hepatitis C infection, HCV-derived core protein associates with the Smad3 MH1 domain inhibiting its DNA-binding activity (Pavio et al, 2005). Smad2 and Smad4 gene mutations have also been identified in 5-10% HCCs (Yakicier et al, 1999;Longerich et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Smad2 mutations occur in 5% of HCCs (Yakicier et al, 1999;Longerich et al, 2004). Inhibitory Smad7 is upregulated in 60% of advanced HCCs (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic point mutations leading to amino-acid substitution in IGF2R or protein truncation were identified in 10-20% of the screened HCC in two series (De Souza et al, 1995;Oka et al, 2002). From another study (Yakicier et al, 1999), rare mutations leading to amino-acid substitutions were identified in MADH2/ Smad2 and MADH4/Smad4 genes (also known as DPC4 or deleted in pancreatic carcinoma 4). They mediate signaling by the TGF-b/activin/BMP-2/4 Genetics of hepatocellular tumors P Laurent-Puig and J Zucman-Rossi cytokine superfamily from receptor serine/threonine protein kinases at the cell surface to the nucleus (Lagna et al, 1996;Liu et al, 1996).…”
Section: )mentioning
confidence: 99%
“…ductal pancreatic adenocarcinoma with Smad4 mutations in about 50%), seems to be intact in the vast majority of human HCCs. Smad2 mutations (o5%) and loss of Smad4 expression (10%) are infrequent molecular events (Yakicier et al, 1999;Longerich et al, 2004). Smad3 mutations have not been described in human hepatocarcinogenesis yet; however, recently published data clearly show a physical interaction between Smad3 and the HCV core protein, consequently antagonizing DNA-binding capacity of Smad3 and therefore reducing TGFb-dependent signaling (Cheng et al, 2004;Pavio et al, 2005).…”
Section: Transforming Growth Factor B Signaling Axismentioning
confidence: 99%